Plasma Aβ and PET PiB binding are inversely related in mild cognitive impairment - Devanand, D.P. (Lippincott Williams & Wilkins, 2011)
OBJECTIVE: To evaluate the relations between PET Pittsburgh compound B (PiB-PET) binding (amyloid imaging) and plasma Aβ in patients with mild cognitive impairment (MCI) and similarly aged controls. METHODS: In 20 patients with MCI and 19 cognitively intact controls (case-control study), PiB binding potential (BP(nd)) was assessed in 4 regions, and total brain excluding cerebellum, referenced to cerebellar binding. The mean of plasma Aβ levels measured in duplicate was analyzed. RESULTS: Plasma Aβ42/Aβ40 ratio was decreased in MCI compared to controls (mean 0.15 SD 0.04 vs mean 0.19 SD 0.07, p = 0.03) but Aβ40 (p = 0.3) and Aβ42 (p = 0.06) levels did not differ between the 2 groups. PiB BP(nd) was increased in MCI compared to controls in the cingulate (p = 0.02), parietal (p = 0.02), and total brain (p = 0.03), but not in prefrontal cortex (p = 0.08) or parahippocampal gyrus (p = 0.07). Linear regression analyses adjusting for age, sex, and cognitive test scores showed that low Aβ42/Aβ40 ratio was associated with high cingulate, parietal, and total brain PiB binding (0.01< p ≤ 0.05). These associations between PiB binding and the Aβ42/Aβ40 ratio were strongest in PiB-positive subjects and within the MCI group. CONCLUSIONS: Though cross-sectional, the findings support the “sink” hypothesis that increased brain Aβ is accompanied by lower peripheral levels of Aβ, particularly the Aβ42/Aβ40 ratio in patients with MCI. The association between PiB binding and the plasma Aβ42/Aβ40 ratio suggests possible use of plasma Aβ combined with PiB binding as a risk biomarker with potential clinical application.